The New Economy and the International Regulatory Framework - Daniel Piazolo (Kiel Institute of World Economics (IfW), 2001)
The rapid diffusion of the internet and electronic commerce changes the way business and international trade take place. The new economy poses new challenges to the international regulatory framework, since small distortions due to differing sets of regulations and taxation between countries might grow to non-negligible dimensions. This paper examines the necessary reforms of the multilateral framework concerning standards, policy coordination and taxation and stresses that the new economy reinforces the need for consistent, transparent, non-discriminatory, simple and enforceable rules. Furthermore, strategies to overcome the digital divide between countries are set out.
Keywords: O3; O19; F02; 330; New Economy; Policy Coordination; Tax Distortion; Trade Diversion; WTO; Developing Countries; New Economy; E-Business; Internet; Normung; Ursprungslandprinzip; Internationale Zusammenarbeit; Internationales Steuerrecht; WTO-Regeln; Welt